Enhancing Character and critical thingking skills trough multiliteracy and multicontext models in independent learning: A study in high school in East Java, Indonesia - Amil Ahmad Jami’ul; Ismail Nor Hasimah; Narawi Mohammad Syawal (BIO Web of Conferences)
Multiliteracy and multicontext learning are evolving approaches essential for strengthening character and fostering high-level thingking skills in the context of independent learning. This study aims to explore how multiliteracy and multicontext models can enhance character development and high-level thingking skills in high school students. Multiliteracy in character education, particularly through literary literacy (novels) and context teaching, is crucial for shaping personality and enhancing critical thinking in an era of disruption. Utilizing qualitative methods including literature review and phenomenology, this study analyzes document data form journals, books, and field sources. Time triangulation and atlas.ti9 ensure the reliability of the results. The study finds that multiliteracy and multicontext teaching models, involving dialouge, monologue, and practical activities, effectively enchance students’ high-level thinking skills. Effective approaches include integrating learning communities, online and offline classes, practical projects, and problem-solving avtivities. The use of modern Indonesian literary texts and multicontext teaching has proven effective in promoting avtive, student-centered learning and enhancing critical thinking. Future research should focus on the impact of multiliteracy on character development and critical thinking, as well as strategies for integrating contextual learning with industry practices. Overall, multiliteracy and multicontext teaching models effectively build high-level thinking skills and character, offering valuable opportunities for professional development.